The evolving rhetoric of marine le pen. (c2018) - Chidiac, Sarah Omar (2018)
With the brisk rise of the Five Star Movement in Italy, the emergence of Law and Justice as the largest party in the Polish parliament, and the entrance of the Alternative for Deutschland as the third largest bloc in the German Bundestag, the eyes of the world were centered on the 2017 French presidential election. The French Presidential election could have ended with the inauguration of Marine Le Pen, leader of the National Front, as president of the French Republic. As populism and nationalism swept away one European country after the other, it was reasonable to think that the French far right had a real chance to rule. Despite having lost to current president Emmanuel Macron, Le Pen’s second place in the race was considered a remarkable achievement to her and her party. This thesis explores the politician’s rhetoric and how it has evolved across the years. It examines various speeches made by Le Pen on different occasions, starting with the year 2010, during which she campaigned for the presidency of the National Front, to 2017, only a few days prior to the presidential election. The purpose of this examination is to understand and to depict the rhetoric manipulation techniques that have had the ability to conceal the blatant tenets of Le Pen’s political discourse. This thesis also endeavors to show how Le Pen’s communication of the same old message in a different method was executed to manipulate the French people’s votes. The thesis employs a comparative approach to the analysis of different speeches of Le Pen in order to capture her rhetoric style and ideology.